Quantificação do processo de osteogênese em implantes dentários - Oliveira, Lidiane Sartini de (2010)
Dental implants appeared as an alternative for replacing missing teeth. The first dental implants were based on empiricism and were unsuccessful because of the lack of controlled clinical trials and scientific studies. In the 1960 s Brånemark and colleagues, based on clinical research developed a new implant system using a direct anchorage in the bone structure, without an interposed having soft tissue, called osseointegration. The osseointegration process involves biomechanical aspects and it is not yet completely understood. In various studies it has been verified that the implat surface treatment, for example, surfaces treated with sandblasting and acid etching, has shown itself to be one of the principal factors influencing osteogenesis and consequently osseointegration. Such surfaces offer conditions appropriate for a quicker bone apposition, thus making load application possible in a shorter period of time. Therefore, the purpose of this study was to evaluate the osteogenesis phenomenon in dental implants, taking into consideration the different surfaces obtained through differing sandblasting and acid etching conditions. An evaluation was carried out using in vitro experiments of osteoblastic cell culture. An osseointegration index was defined to measure the intensity of the osteogenesis based on calculations of cell viability and proliferation, alkaline phosphatase activity and mineralized nodules formation. The experiments were conducted in such a way that the sensitivity of the varios measures would be analyzed and, by means of similar methods in engineering, a predictable equation was defined for the phenomenon. The advantage of this procedure is the possibility of foreseeing the osteogenesis level, without resorting to experiments in vivo and in vitro which, in general are time consuming and costly, making it possible to evaluate a product, with respect to its surface conditions before putting it on the market, thus serving as a quality control tool .